2004
DOI: 10.1038/sj.bjp.0705973
|View full text |Cite
|
Sign up to set email alerts
|

GW9662, a potent antagonist of PPARγ, inhibits growth of breast tumour cells and promotes the anticancer effects of the PPARγ agonist rosiglitazone, independently of PPARγ activation

Abstract: Peroxisome proliferator-activated receptor gamma (PPARg), a member of the nuclear receptor superfamily, is activated by several compounds, including the thiazolidinediones. In addition to being a therapeutic target for obesity, hypolipidaemia and diabetes, perturbation of PPARg signalling is now believed to be a strategy for treatment of several cancers, including breast. Although differential expression of PPARg is observed in tumours compared to normal tissues and PPARg agonists have been shown to inhibit tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
121
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 14 publications
16
121
1
Order By: Relevance
“…Despite the fact that GW9662 fully reversed cannabidiol's inhibitory effect on A549 xenograft growth, the substance caused a pronounced tumor-regressive action when administered alone. Similar ambiguous findings have been reported in vitro where the PPAR-g agonist rosiglitazone and the PPAR-g antagonist GW9662 inhibited the growth of breast cancer cells to similar extents (36). In fact, PPAR-g antagonists have been shown to confer PPARg-independent antiproliferative, antiadhesive, and antimetastatic actions (for review see ref.…”
Section: Discussionsupporting
confidence: 71%
“…Despite the fact that GW9662 fully reversed cannabidiol's inhibitory effect on A549 xenograft growth, the substance caused a pronounced tumor-regressive action when administered alone. Similar ambiguous findings have been reported in vitro where the PPAR-g agonist rosiglitazone and the PPAR-g antagonist GW9662 inhibited the growth of breast cancer cells to similar extents (36). In fact, PPAR-g antagonists have been shown to confer PPARg-independent antiproliferative, antiadhesive, and antimetastatic actions (for review see ref.…”
Section: Discussionsupporting
confidence: 71%
“…mine if the effects of probiotics on the epithelial barrier and cytokine secretion were dependent on PPAR␥ activation, a group of mice were treated with a selective PPAR␥ antagonist, GW9662, 30 minutes before LPS/GalN injection. 28 As shown in Fig. 8, the inhibition of PPAR␥ abrogated the ability of probiotics to protect against an LPS/GalN-induced breakdown in colonic barrier function and cytokine secretion.…”
Section: Resultsmentioning
confidence: 75%
“…One possibility for the requirement of very high doses to inhibit cell viability is that the endogenous PPARg receptors, which are often overexpressed in cancer, may need to be saturated prior to intracellular levels of TZD rising sufficiently to mediate anti-tumour effects. Indeed, Seargent et al (2004) demonstrated that the PPARg antagonist GW9662 selectively occupied PPARg receptors, yet enhanced rosiglitazone's anti-tumour effects in breast cancer cells, supporting the concept that by binding to PPARg, GW9662 permitted a higher intracellular level of rosiglitazone (Seargent et al 2004). Alternatively, the amount of TZD that can enter a tumour cell may be limited.…”
Section: Discussionmentioning
confidence: 91%